Validation of the Awareness Atlas—a new measure of the manifestation of consciousness - Jia, Yuane; Schenkman, Margaret; O Connor, Hester; Jayanna, Krishnmurthy; Pearmain, Rosalind; Van’t Westeinde, Annelies; Patel, Kamlesh D. (Frontiers in Psychology, 2024)
Consciousness has intrigued philosophers and scholars for millennia and has been the topic of considerable scientific investigation in recent decades. Despite its importance, there is no unifying definition of the term, nor are there widely accepted measures of consciousness. Indeed, it is likely that consciousness-by its very nature-eludes measurement. It is, however, possible to measure how consciousness manifests as a lived experience. Yet here, too, holistic measures are lacking. This investigation describes the development and validation of the Awareness Atlas, a measure of the manifestation of consciousness. The scale was informed by heart-based contemplative practices and the resulting lived experience with a focus on the impacts of manifestation of consciousness on daily life. Four hundred forty-nine individuals from the USA, Canada, India, and Europe participated in psychometric testing of the scale. Exploratory and confirmatory factor analyses were used for validation, demonstrating excellent validity in measuring manifestation of consciousness. The final model fit exceeded all required thresholds, indicating an excellent fitted model with a single dimensionality to measure the manifestation of consciousness comprised of four subscales: Relationship to Others; Listening to the Heart; Connection with Higher Self; and Acceptance and Letting Go. Number of years meditating and practicing Heartfulness meditation were positively related to the total and subscale scores. Testretest reliability was excellent for the total scale, and good to excellent for the four subscales. Findings demonstrate that the Awareness Atlas is a well-constructed tool that will be useful in examining changes in manifestation of consciousness with various experiences (e.g., meditation, life-altering conditions).